Critical Review of Domestic Violence as Reason for Divorce (Comparison of Divorce Laws in Indonesia, Malaysia and the Maldives) - Martina Purna Nisa (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2021)
The phenomenon of domestic violence is on the rise every year and often puts a marriage into divorce. Divorce on the grounds of domestic violence frequently appears in the courtroom of Religious Courts in Indonesia as stipulated in Article 19 letter d PP No. 9 of 1975. It affirms that one party committing cruelty or severe persecution that endangers another party can be the legal reason for divorce. And then what about other Muslim countries? This research is library research with a descriptive-analytical method using a juridical normative approach. It found that domestic violence is accommodated as one of the reasons for divorce in family law in Indonesia, Malaysia (Negeri Sembilan, Persekutuan Pulau Pinang, Selangor dan Johor), and the Maldives. However, there are differences in granting the right for filing a divorce because of domestic violence. Divorce law in Indonesia and Malaysia enables both husband and wife to file for divorce because of domestic violence while Maldives law only enables the wife to do so. Fenomena kekerasan dalam rumah tangga selalu meningkat setiap tahunnya dan seringkali menjadi sebab perceraian. Perceraian karena kekerasan dalam rumah tangga sering muncul di ruang sidang pengadilan agama di Indonesia. Ini sebagaimana diatur dalam Pasal 19 huruf d PP No. 9 Tahun 1975 bahwa salah satu pihak yang melakukan kekejaman atau penganiayaan berat yang membahayakan pihak lain dapat menjadi alasan hukum terjadinya perceraian. Lalu bagaimana dengan di negara-negara Muslim lainnya? Penelitian ini termasuk dalam penelitian pustaka (library research) yang bersifat deskriptif analitis dengan pendekatan normatif yuridis. Dalam penelitian ini diperoleh temuan bahwa kekerasan dalam rumah tangga diakomodir sebagai alasan perceraian dalam hukum keluarga di Indonesia, Malaysia (Negeri sembilan, Persekutuan Pulau Pinang, Selangor dan Johor), maupun Maladewa. Hanya saja, terdapat perbedaan dalam hak mengajukan perceraian karena kekerasan dalam rumah tangga. Hukum perceraian di Indonesia dan Malaysia membolehkan kedua belah pihak untuk mengajukan perceraian karena kekerasan dalam rumah tangga, sementara hukum Maladewa hanya memungkinkan pihak istri.